The Diez albums - Gonnella, Julia.; Weis, Friederike.; Rauch, Christoph. (Islamic Manuscripts and Books, 2016)
The five Diez albums in Berlin, acquired by Heinrich Friedrich von Diez in Constantinople around 1789, contain more than 400 figurative paintings, drawings, fragments, and calligraphic works originating for the most part from Ilkhanid, Jalayirid, and Timurid workshops. Gonnella, Weis and Rauch unite in this volume 21 essays that analyse their relation to their "parent" albums at the Topkapı Palace or examine specific works by reflecting upon their role in the larger history of book art in Iran. Other essays cover aspects such as the European and Chinese influence on Persianate art, aspects related to material and social culture, and the Ottoman interest in Persianate albums. This book marks an important contribution to the understanding of the development of illustrative imagery in the Persianate world and its later perception. Contributors are: Serpil Bağcı, Barbara Brend, Massumeh Farhad, Julia Gonnella, Claus-Peter Haase, Oliver Hahn, Robert Hillenbrand, Yuka Kadoi, Charles Melville, Gülru Necipoğlu, Bernard O'Kane, Filiz Ҫakır Phillip, Yves Porter, Julian Raby, Christoph Rauch, Simon Rettig, David J. Roxburgh, Karin Rührdanz, Zeren Tanındı, Lâle Uluç, Ching-Ling Wang, and Friederike Weis.